SARS-CoV-2 genomic surveillance in Malaysia: displacement of B.1.617.2 with AY lineages as the dominant Delta variants and the introduction of Omicron during the fourth epidemic wave. (December 2022) - Azami, Nor Azila Muhammad; Perera, David; Thayan, Ravindran; AbuBakar, Sazaly; Sam, I-Ching; Salleh, Mohd Zaki; Isa, Mohd Noor Mat; Ab Mutalib, Nurul Syakima; Aik, Wong Kiing; Suppiah, Jeyanthi; Tan, Kim-Kee; Chan, Yoke Fun; et al.
Highlights: The AY.59 and AY.79 strains displaced B.1.617.2 and became the predominant lineage. Different circulating SARS-CoV-2 lineage patterns were seen in the east and west Malaysia. Policies restricting movement and border closure might affect viral transmission. Relaxing the border restrictions aided in the spread of Omicron in Malaysia. Abstract: Objectives: This study reported SARS-CoV-2 whole genome sequencing results from June 2021 to January 2022 from seven genome sequencing centers in Malaysia as part of the national surveillance program. Methods: COVID-19 samples that tested positive by reverse transcription polymerase chain reaction and with cycle threshold values <30 were obtained throughout Malaysia. Sequencing of SARS-CoV-2 complete genomes was performed using Illumina, Oxford Nanopore, or Ion Torrent platforms. A total of 6163 SARS-CoV-2 complete genome sequences were generated over the surveillance period. All sequences were submitted to the Global Initiative on Sharing All Influenza Data database. Results: From June 2021 to January 2022, Malaysia experienced the fourth wave of COVID-19 dominated by the Delta variant of concern, including the original B.1.617.2 lineage and descendant AY lineages. The B.1.617.2 lineage was identified as the early dominant circulating strain throughout the country but over time, was displaced by AY.59 and AY.79 lineages in Peninsular (west) Malaysia, and the AY.23 lineage in east Malaysia. In December 2021, pilgrims returning from Saudi Arabia facilitated the introduction and spread of the BA.1 lineage (Omicron variant of concern) in the country. Conclusion: The changing trends of circulating SARS-CoV-2 lineages were identified, with differences observed between west and east Malaysia. This initiative highlighted the importance of leveraging research expertise in the country to facilitate pandemic response and preparedness.